Learning for Projects in Fundamental Teaching: strategy for understanding food pyramid (Research, Society and Development, 2019)
This study aims to assess the knowledge of the food pyramid for school year the students of final grades of primary school, as well as a proposal for how learning designs can influence the acquisition of these concepts by students. This is a case study in the city of Santa Maria / RS, with students from 6th to 9th grade of a public state school, totaling 158 students. The students answered two questions about the food pyramid be imagined. In both responses, found a better result on the 6th and 8th grade, but students' understanding of the 6th year achieved a marked improvement in post-test, and this could indicate that the projects developed by teachers in these two groups have obtained best meaningful learning by students.